1997
DOI: 10.1897/1551-5028(1997)016<1028:ttomtu>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of Malathion to Unionid Mussels: Relationship to Expected Environmental Concentrations

Abstract: The acute toxicity of malathion to glochidia, juvenile, and adult freshwater mussels was determined at pH 7.5 in soft water and at pH 7.9 in moderately hard reconstituted fresh water at 25ЊC and 32ЊC. Nine species were tested in one or more life stages. Glochidia tests were conducted for 4, 24, or 48 h, while juvenile and adult exposures lasted 96 h. Overall, Utterbackia imbecillis was the least sensitive species for all exposure conditions and life stages. The LC50 values for glochidia tested at 25ЊC ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Data generated by our laboratories generally followed protocols published by us for mussel toxicity tests with other compounds [8]. Static toxicity tests were 24-to 96-h exposures with glochidia or juvenile stages of mussels.…”
Section: Development Of the Ammonia Toxicity Databasementioning
confidence: 99%
“…Data generated by our laboratories generally followed protocols published by us for mussel toxicity tests with other compounds [8]. Static toxicity tests were 24-to 96-h exposures with glochidia or juvenile stages of mussels.…”
Section: Development Of the Ammonia Toxicity Databasementioning
confidence: 99%
“…Published toxicological data indicate that early life stages of freshwater mussels (glochidia and juveniles) are among the most sensitive aquatic organisms to contaminants such as ammonia [3][4][5], metals [6], and some pesticides [7]. In contrast, early life stages of mussels have been reported to be less sensitive to some pesticides compared to other aquatic invertebrates such as amphipods, chironomids, and cladocerans [7][8][9]. Because spring/summer agricultural pesticide applications often coincide with the reproductive period of native freshwater mussels, early life stages of mussels may be exposed to high concentrations of pesticides due to overspray or runoff.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found the larval glochidia of certain unionid species including V. iris are more sensitive than juveniles to various toxicants (Keller and Ruessler 1997;Augspurger et al 2003;Valenti et al 2005). Physiological advantages of juvenile mussels may also contribute to their tolerance of toxicological stressors.…”
Section: Discussionmentioning
confidence: 99%